Visual outcomes after optic exchange of a modular intraocular lens. Issue 11 (November 2021) - Ang, Robert Edward T.; Yoo, Paul; Liu, Jingbo
Abstract : An IOL with an exchangeable optic provided visual outcomes comparable with a monofocal IOL; optic exchange improved visual outcomes for subjects who did not achieve optimal vision after initial implantation. Abstract : Purpose: To evaluate the effectiveness of the Harmoni Modular IOL (HMIOL). Setting: 3 study sites. Design: Prospective, multicenter clinical study. Methods: HMIOL is a foldable, posterior chamber lens with separate base and exchangeable optic components. Eligible adults undergoing cataract surgery received HMIOL in the study eye (monovision target −1.50 diopters [D]) and standard monofocal IOL in contralateral eye (control). After 3 months, subjects could undergo optic exchange based on visual outcomes. End points included uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), and manifest refractive spherical equivalent (MRSE). Follow-up was 12 months or greater postoperatively. Results: 114 subjects had successful HMIOL implantation in study eye and control IOL in contralateral eye. At 3 months, subjects could undergo optic exchange if unsatisfied with monovision; 65 eyes had optic exchange (exchange cohort), and 49 eyes had no exchange (no exchange cohort). In exchange cohort, the proportion of eyes with UDVA of 20/40 or greater and of 20/20 or greater increased 3 months after optic exchange vs preexchange levels by 23% (97% vs 74%) and 40% (49% vs 9%), respectively. In all cohorts, 95% of subjects or greater achieved UDVA of 20/40 or greater after 12 months or greater. Control and no exchange cohorts achieved CDVA of 20/40 or greater by 3 months; 97% of eyes or greater had CDVA of 20/40 or greater at 12 months after optic exchange. In exchange cohort, the proportion of eyes with MRSE within ±0.50 D and ±1.00 D of target changed by 57% and 36%, respectively, from preexchange (20% and 59%, respectively) to 12 months postexchange (77% and 95%, respectively), reaching levels similar to control subjects (72% and 97%, respectively). Conclusions: HMIOL provided visual outcomes comparable with standard monofocal IOLs.